Design and development of a carbon dioxide gas generator for firefighting robot application - Ajala, Mosud Taiwo; Khan, Md. Raisuddin; Shafie, Amir Akramin; Salami, Momoh Jimoh-Eyiomioka; Oladokun, Majeed Olaide; Maizirwan, Mel; Mohamad Nor, Mohamad Iskandar (IET, 2022)
The drawbacks in the performance of electric actuated firefighting robots in high-temperature fire environments steered research on the alternative propulsion system for the mobility of firefighting robots in such a situation. Exploiting the limitations of the electric actuators, a carbon dioxide gas-actuated propulsion system has been developed. The propulsion system is composed of a pneumatic motor and a carbon dioxide gas-power source. The pneumatic motor is used as an actuator in the robotic firefighting system, and it is powered by carbon dioxide gas (in place of the conventional ‘air”), which is self-generated from dry ice within the robotic system.